Effect of the supplementation of mashua (Tropaeolum tuberosum) and tarwi (Lupinus mutabilis) meal on the productive response and nutritional composition of guinea pigs (Cavia porcellus) - Acuña Beraun, Sayuri Rosangela (2021)
The effect of supplementation with mashua (Tropaeolum tuberosum) and tarwi (Lupinus mutabilis) meal on body weight gain (BWG), feed consumption, feed conversion index and nutritional composition of carcasses of Peru breed guinea pigs was evaluated. Peru. For the study, 32 4-week-old male guinea pigs (309-578 g) were randomly distributed in four treatments (T) for 40 days: T1 (integral concentrate - IC), T2 (CI + 18% tarwi), T3 (IC + 25 % mashua) and T4 (I C+ 25% mashua + 18% tarwi). Supplementation with tarwi meal (T2 and T4) improved BWG, while supplementation with mashua meal (T3) had a significant effect on carcass fat content (p<0.05). There was no effect on feed consumption and feed conversion.